Nutrition training roadmap for administrators across India - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
IFPRI researchers, development partners, implementers and nutrition experts developed the roadmap collaboratively in 2019. The next step will be implementing it. Content development for nutrition training using three modalities- face-to-face, online, and a blended model - is ongoing, along with discussions to operationalize the online version of the nutrition training.